The ScCas9++ variant expands the CRISPR toolbox for genome editing in plants. Issue 9 (10th September 2021) - Liu, Taoli; Zeng, Dongchang; Zheng, Zhiye; Lin, Zhansheng; Xue, Yang; Li, Tie; Xie, Xianrong; Ma, Genglu; Liu, Yao‐Guang; Zhu, Qinlong
Abstract: The development of clustered regularly interspaced palindromic repeats (CRISPR)‐associated protein (Cas) variants with a broader recognition scope is critical for further improvement of CRISPR/Cas systems. The original Cas9 protein from Streptococcus canis (ScCas9) can recognize simple NNG‐protospacer adjacent motif (PAM) targets, and therefore possesses a broader range relative to current CRISPR/Cas systems, but its editing efficiency is low in plants. Evolved ScCas9 + and ScCas9 ++ variants have been shown to possess higher editing efficiencies in human cells, but their activities in plants are currently unknown. Here, we utilized codon‐optimized ScCas9, ScCas9 + and ScCas9 ++ and a nickase variant ScCas9n ++ to systematically investigate genome cleavage activity and cytidine base editing efficiency in rice ( Oryza sativa L.). This analysis revealed that ScCas9 ++ has higher editing efficiency than ScCas9 and ScCas9 + in rice. Furthermore, we fused the evolved cytidine deaminase PmCDA1 with ScCas9n ++ to generate a new evoBE4max‐type cytidine base editor, termed PevoCDA1‐ScCas9n ++ . This base editor achieved stable and efficient multiplex‐site base editing at NNG‐PAM sites with wider editing windows (C− 1 –C17 ) and without target sequence context preference. Multiplex‐site base editing of the rice genes OsWx (three targets) and OsEui1 (two targets) achieved simultaneous editing and produced new rice germplasm. Taken together, these results demonstrate that ScCas9 ++ represents a crucial new tool for improving plant editing. Abstract : The nuclease ScCas9 recognizes the protospacer‐adjacent motif NNG, but its editing activity is low in plants. However, the engineered evolved ScCas9 ++ has higher editing efficiency than other ScCas9 variants in rice and its nickase variant ScCas9n ++ has improved potential for developing base‐editing tools with expanded target scope in plants.